Elevated aqueous humour tissue inhibitor of matrix metalloproteinase-1 and connective tissue growth factor in pseudoexfoliation syndrome. Issue 2 (21st January 2005) - Ho, S L; Dogar, G F; Wang, J; Crean, J; Wu, Q D; Oliver, N; Weitz, S; Murray, A; Cleary, P E; O'Brien, C
Abstract : Background/aims: Pseudoexfoliation syndrome (PXF) was recently found to be associated with increased expression of transforming growth factor β1 (TGFβ1 ) in the aqueous humour. As concern has been raised regarding anti-TGFβ therapy, which can potentially disrupt the maintenance of anterior chamber asso-ciated immune deviation, the authors explored the levels of tissue inhibitor of matrix metalloproteinase-1 (TIMP-1), matrix metalloproteinase-9 (MMP-9), and connective tissue growth factor (CTGF) in aqueous humour to determine if these may represent alternative therapeutic targets. Methods: Aqueous humour samples were collected from patients who underwent routine cataract surgery. All patients were categorised into three main groups—PXF, uveitis, and control. The PXF group was further subcategorised into three grades based on the density of the exfoliative material observed on biomicroscopy, as well as the presence or absence of glaucoma. TIMP-1, MMP-9, and CTGF levels were measured using specific enzyme immunoassays (ELISA). Results: Eyes with PXF had significantly higher aqueous humour TIMP-1 concentration (n = 56, mean (SE), 9.76 (1.10) ng/ml) compared with controls (n = 112, 5.73 (0.43) ng/ml, p<0.01). Similarly, the CTGF level in PXF eyes (n = 36, 4.38 (0.65) ng/ml) was higher than controls (n = 29, 2.35 (0.46) ng/ml, p<0.05). Further, the CTGF concentration in the PXF glaucoma group is significantly higher compared with PXF eyes without glaucoma (6.03 (1.09) ng/ml v 2.73 (0.45) ng/ml, p<0.01). The MMP-9 levels were low and below detection limit in all PXF and control samples with no statistical difference between groups. Conclusion: A raised TIMP-1 level and a low MMP-9 level in aqueous humour of PXF eyes may imply a downregulation in proteolytic activity. The increased CTGF concentration supports the proposed fibrotic pathology of PXF. Regulation of MMP/TIMP expression and anti-CTGF therapy may offer potential therapeutic avenues for controlling PXF associated ocular morbidity.